2015
DOI: 10.1161/circoutcomes.114.001381
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Replicating Trials of Exercise-Based Cardiac Rehabilitation

Abstract: Background-Complete reporting of all components of complex interventions is essential for translation of research evidence into clinical practice. Previous work has highlighted deficiencies in the reporting of nonpharmacological interventions; however, the reporting quality of exercise-based interventions for coronary heart disease has not been examined. Methods and Results-A systematic search strategy was used to identify randomized controlled trials of exercise-based cardiac rehabilitation published until De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 38 publications
11
100
0
Order By: Relevance
“…Similar to previous findings (Abell, Glasziou, & Hoffmann, 2015;Bryant, Passey, Hall, & Sanson-Fisher, 2014;Hoffmann et al, 2013;Pino, Boutron, & Ravaud, 2012), our results highlight that details about the materials used in the delivery of interventions and in the training of intervention providers were the most poorly reported. Home programs were a key component in many upper limb studies, and one study directly investigated their efficacy (Novak, Cusick, & Lannin, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to previous findings (Abell, Glasziou, & Hoffmann, 2015;Bryant, Passey, Hall, & Sanson-Fisher, 2014;Hoffmann et al, 2013;Pino, Boutron, & Ravaud, 2012), our results highlight that details about the materials used in the delivery of interventions and in the training of intervention providers were the most poorly reported. Home programs were a key component in many upper limb studies, and one study directly investigated their efficacy (Novak, Cusick, & Lannin, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Reporting of the research intervention setting/location in over half of the trials is similar to previous studies (Abell et al, 2015;Hoffmann et al, 2013). Although tailoring was more highly reported in these paediatric trials of upper limb interventions and reflected individualisation related to collaborative goal setting, the specific details of how tailoring was done and how interventions were progressed was not thoroughly described.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…An analysis of the reporting of the exercise component used in cardiac rehabilitation trials found that adequate descriptions of the exercise schedule were missing for 58% of the interventions. 7 We summarize evidence of benefit for using exercise for some key chronic conditions, highlight key outcomes shown to be influenced by exercise and provide a guide to the practical howto details for an effective disease-specific exercise. We discuss conditions that were selected for their high disability burden 8 and the strength of the evidence for the effectiveness of exercise in managing the condition.…”
mentioning
confidence: 99%
“…For Item 5 -Intervention Provider-we required a clear description of who supervised the exercise sessions, including what specific training they received in delivering the intervention, and a description of their Table 1. Brief description of the Template for Intervention Description and Replication (TIDieR) items that were used to assess intervention reporting (adapted from refs [22] and [23]). Describe any strategies, besides direct supervision, which were used to maintain or improve intervention fidelity…”
Section: Assessment Of Intervention Descriptionmentioning
confidence: 99%